Kampanie wyborcze kandydatów w wyborach prezydenckich w Ukrainie w 2019 r. - Taranenko, Bohdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article analyses the election campaigns of the candidates in the 2019 presidential election in Ukraine. The analysis focuses on the impact of the candidates "image on voters" decisions, the role of the media and the debate. The aim of the article is to understand the reasons that led to Volodymyr Zelensky`s victory in the elections. Particular attention is given to analysing the image of the "simple man of the people" used by Volodymyr Zelensky during the campaign.
Keywords: wybory; Ukraina; kampania wyborcza; prezydent; wizerunek; elections; Ukraine; election campaign; president; image